Recent centennial drought on the Tibetan Plateau is outstanding within the past 3500 years - Yu Liu; Huiming Song; Zhisheng An; Qiang Li; Steven W. Leavitt; Ulf Büntgen; Qiufang Cai; Ruoshi Liu; Congxi Fang; Changfeng Sun; Kerstin Treydte; Meng Ren; et al. (Nature Communications)
Abstract Given growing concerns about global climate change, it is critical to understand both historical and current shifts in the hydroclimate, particularly in regions critically entwined with global circulation. The Tibetan Plateau, the Earth’s largest and highest plateau, is a nexus for global atmospheric processes, significantly influencing East Asian hydroclimate dynamics through the synergy of the Asian Monsoon and the Westerlies. Yet, understanding historical and recent hydroclimate fluctuations and their wide-ranging ecological and societal consequences remains challenging due to short instrumental observations and partly ambiguous proxy reconstructions. Here, we present a precisely-dated 3476-year precipitation reconstruction derived from tree-ring δ18O data on the Tibetan Plateau, representing one of the few multi-millennia-long annually-resolved terrestrial δ18O records to date. Our findings reveal that the 20th century drought extremes are severe within the past three millennia, and likely linked to the weakening of both the Asian Monsoon and Westerlies due to anthropogenic aerosol emissions. Additionally, our analyses identified three distinct stages (110 BC–AD 280, AD 330–770 and AD 950–1300) characterized by shifts toward arid hydroclimate conditions, corresponding to significant social unrest and dynasty collapses, which underscores the potential societal impacts of severe hydroclimatic shifts.